Effect of gas–liquid ratio on the wall shear stress in slug flow in capillary membranes. Issue 6 (17th October 2018) - Kumari, Sadhana; Kumar, Nilay; Gupta, Raghvendra
Abstract: The membrane processes generally suffer from the fouling caused by the deposits at the membrane surface and membrane pores. In recent years, gas–liquid flow has been shown to be an effective method of membrane fouling prevention. Among the different flow regimes that occur during gas–liquid flow through membrane capillaries, slug flow has been observed to be the most effective for enhancement of permeate flux. The shearing caused by the fluid on the membrane wall is the primary factor causing fouling removal. Previous studies in the slug flow regime suggest that the major contribution to the wall shear stress comes from the bubble front and rear regions and the contribution from the constant film thickness region in the middle is negligible. Therefore, the average wall shear stress in the slug flow regime is dependent on the bubble length. In this work, two‐phase gas–liquid flow in a capillary has been modeled computationally to understand the effect of bubble length on the wall shear stress. Further, the effect of liquid viscosity on the wall shear stress has also been studied for capillary numbers ranging from 0.0037 to 0.098. The volume‐of‐fluid method has been employed to capture the gas–liquid interface between the two phases. The results have been compared with a simple phenomenological model for wall shear stress available in literature and found to be in good agreement for long Taylor bubbles.